Evaluation of a rare glucose‐dependent insulinotropic polypeptide receptor variant in a patient with diabetes. Issue 5 (19th February 2019) - Jacobi, Simon F.; Khajavi, Noushafarin; Kleinau, Gunnar; Teumer, Alexander; Scheerer, Patrick; Homuth, Georg; Völzke, Henry; Wiegand, Susanna; Kühnen, Peter; Krude, Heiko; Gong, Maolian; Raile, Klemens; et al.
Abstract : Aims: Glucose‐dependent insulinotropic polypeptide (GIP) is an incretin hormone that augments insulin secretion in pancreatic β‐cells via its glucose‐dependent insulinotropic polypeptide receptor (GIPR). Recent genome‐wide association studies identified a single nucleotide variant (SNV) in the GIPR encoding gene ( GIPR ), rs1800437, that is associated with obesity and insulin resistance. In the present study, we tested whether GIPR variants contribute to obesity and disturb glucose homeostasis or diabetes in specific patient populations. Materials and methods: Exon sequencing of GIPR was performed in 164 children with obesity and insulin resistance and in 80 children with paediatric‐onset diabetes of unknown origin. The Study of Health in Pomerania (SHIP) cohort, comprising 8320 adults, was screened for the GIPR variant Arg217Leu. GIPR variants were expressed in COS‐7 cells and cAMP production was measured upon stimulation with GIP. Cell surface expression was determined by ELISA. Protein homology modelling of the GIPR variants was performed to extract three‐dimensional information of the receptor. Results: A heterozygous missense GIPR variant Arg217Leu (rs200485112) was identified in a patient of Asian ancestry. Functional characterization of Arg217Leu revealed reduced surface expression and signalling after GIP challenge. The homology model of the GIPR structure supports the observed functional relevance of Arg217Leu. Conclusion: In vitro functional studies and protein homology modelling indicate a potential relevance of the GIPR variant Arg217Leu in receptor function. The heterozygous variant displayed partial co‐segregation with diabetes. Based on these findings, we suggest that GIPR variants may play a role in disturbed glucose homeostasis and may be of clinical relevance in homozygous patients.